1984
DOI: 10.1007/bf03189684
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and pharmacokinetics of metaclazepam (Talis®), Part III: Determination of the chemical structure of metabolites in dogs, rabbits and men

Abstract: The metabolism of 7-bromo-1-methyl-2-methoxymethyl-5-(2'-chlorophenyl)-2, 3-dihydro-1H-1,4-benzodiazepine (metaclazepam, Talis) in animals and men is described. Based upon mass spectrometry fifteen metabolites could be identified. Qualitative and quantitative differences in the biotransformation products of metaclazepam in comparison with the well known metabolites of other drugs in the 1,4-benzodiazepine class could be demonstrated. Metabolites with a benzodiazepine-2-one structure representing the most chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Because of its high sensitivity and specificity, mass spectrometry has been used widely to characterize several 1,4and 1,5-benzodiazepine derivatives [5][6][7][8][9], as well as to elucidate their biotransformation pathways and pharmacokinetics [10,11]. Mass spectrometric characterization of fused benzodiazepines, such as imidazo- [12,13], pyrrolo- [14], s-triazolo-benzodiazepines [15], and dibenzodiazepines [16][17][18] also has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its high sensitivity and specificity, mass spectrometry has been used widely to characterize several 1,4and 1,5-benzodiazepine derivatives [5][6][7][8][9], as well as to elucidate their biotransformation pathways and pharmacokinetics [10,11]. Mass spectrometric characterization of fused benzodiazepines, such as imidazo- [12,13], pyrrolo- [14], s-triazolo-benzodiazepines [15], and dibenzodiazepines [16][17][18] also has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Several important mass spectra have been et al [7]. GLC on a 165 cmx 2 mm OV-101 column and a 148 cm x 2 mm OV-17 column in a Varian Aerograph, Series 2100, instrument, with Gas Chrom Q as support and nitrogen as carrier gas, FID detection, oven temperature 250 ~ or 280 ~ and injection port and detector at 300 ~ gives the Kov~ts retention indices shown below.…”
Section: Other Methods For Screening and Detection Of Metaclazepammentioning
confidence: 99%
“…The biotransformation of metaclazepam has been extensively studied by Borchers et al [7], who isolated and identified 15 metabolites. Fig.…”
Section: Biotransformation and Important Pharmacokinetic Datamentioning
confidence: 99%
See 1 more Smart Citation